Metabolic reprogramming of multipotent mesenchymal stromal cells in three-dimensional spheroids - Olena Rogulska; Eliska Vavrinova; Oleg Lunov; Katarina Smolkova; Yuriy Petrenko (Stem Cell Research & Therapy, 2026)
Abstract Background Three-dimensional (3D) spheroid culture has emerged as a promising approach to enhance the therapeutic potential of multipotent mesenchymal stromal cells (MSCs). However, the metabolic mechanisms underlying the functional performance of spheroid MSCs remained poorly defined. In this study, we provide an integrative metabolic characterization of human adipose tissue-derived MSCs during spheroid formation and culture. Methods Human adipose tissue–derived MSCs were cultured as 3D spheroids and analyzed during formation and 7 days’ culture. Cellular bioenergetics were assessed using Seahorse extracellular flux analysis. Global metabolic changes were characterized by untargeted liquid chromatography–mass spectrometry (LC–MS) based metabolomics and lipidomics. Secretion of growth factors was quantified using a Luminex-based multiplex immunoassay. Lipidomic profiles of MSC spheroids were further compared with released extracellular particles. Results Spheroid culture induced progressive cellular compaction, reduced cell size, and enhanced secretion of pro-regenerative growth factors. Bioenergetics analysis revealed a marked suppression of both oxidative phosphorylation and glycolysis compared with monolayer cultures, indicating a shift toward a quiescent-like metabolic state. Metabolomic profiling demonstrated reduced intracellular amino acid levels, consistent with decreased demand for protein synthesis. Lipidomic analysis revealed extensive lipid remodeling, characterized by enrichment of diacylglycerols and unsaturated fatty acids alongside a pronounced reduction in structural phospholipids. Comparative lipidomic profiling showed substantial overlap between spheroids and the released large extracellular particles, suggesting particle-mediated lipid export. Conclusions MSC spheroid formation is accompanied by dynamic metabolic reprogramming involving bioenergetic suppression, altered amino acid utilization, and extensive lipid remodeling. These metabolic adaptations represent a central feature of spheroid MSC biology and provide mechanistic insight into their enhanced therapeutic potential, supporting further optimization of spheroid-based regenerative therapies.